Pre-monsoon maximum temperatures over New Delhi, Mumbai & Chennai and possible solar influence - CHAKRABORTY , P. K.; SRIVASTAVA, K. (MAUSAM, 2006)
Lkkj & o"kZ 1951 ls 2001 rd dh 51 o"kksZa dh vof/k ds fy, ubZ fnYyh] eqEcbZ vkSj psUuS esa ekulwu iwoZ vf/kdre rkieku esa lkekU; fofHkUurkvksa ds lkSj {kksHk [lw;Z ds /kCcksa ¼,l- ,l-½ dh la[;k ds okf"kZd vkSlr ds laca/k esa vkdyu] ds lkFk laHkkfor laca/k dk lkaf[;dh; :Ik ls fo’ys"k.k fd;k x;k gSA rkieku ds Ja`[kykc) vk¡dM+ksa ds vk/kkj ij dsoy psUuS ds fy, rkieku esa o`f) dh izo`fRr dks NksM+dj vU; lHkh dsanzksa ij yxHkx 3 o"kksZa ds vUrjky ij bldh iqujko`fr dk irk pyk gS A lkSj voLFkkvksa ¼o`f) nj fun’kZ dk mi;ksx djds½ dh fofHkUurkvksa ds fo’ys"k.k ls lw;Z dh U;wure vkSj vf/kdre voLFkkvksa ds nkSjku 73 izfr’kr ekeyksa esa rkieku esa o`f) dh izo`fRr dk irk pyk gS A xr o"kZ ds ekulwu iwoZ rkieku vkSj lw;Z ds /kCcksa dh la[;k ds okf"kZd vkSlr ds chp lglaca/k ds xq.kkad :Ik ls ldkjkRed gksus dk irk pyk gS tc lw;Z ds /kCcksa dh la[;k dk okf"kZd vkSlr yxHkx 140 ds pje eku ls vf/kd gks tkrk gS vkSj ;g ¼$0-647½ ubZ fnYyh ds laca/k esa egRoiw.kZ gS A ;g ifj.kke iwohZ Hkkjr ds dsanzksa ds fy, fd, x, blh rjg ds v/;;uksa ds vuq:Ik gS A The general variations of pre-monsoon maximum temperature over New Delhi, Mumbai and Chennai for the 51 years period from 1951 to 2001 and its possible association with solar activity [estimated in terms of annual mean sunspot (SS) numbers] have been analysed statistically. The temperature series indicate an approximate periodicity of 3 years for all the stations with an increasing trend for Chennai only. Analysis of the variations with respect to solar phases (using a growth rate model) indicates an increasing trend of temperature in 73% cases during solar minimum to maximum phases. The correlation coefficient between pre-monsoon temperature and annual mean SS nos. of the preceding year indicate a positive association when the latter exceeds some critical value approximately 140 and it (+0.647) is significant for New Delhi. The present result is consistent with similar studies for stations over eastern India.